Total Synthesis of Bioactive Natural Products by Palladium-Catalyzed Domino Cyclization of Allenes and Related Compounds - Inuki, Shinsuke; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2012)
The author has developed novel methodologies for highly efficient construction of functionalized heterocycles by palladium-catalyzed domino/cascade cyclization of allenes and related compounds containing appropriate nucleophilic group(s). Based on these methodologies, enantioselective total syntheses of bioactive natural products, pachastrissamine (26% overall yield in seven steps), lysergic acid (4.0% overall yield in fifteen steps), lysergol (3.6% overall yield in fifteen steps) and isolysergol (8.2% overall yield in eleven steps) have been achieved. These are more facile synthetic route than those previously reported. These findings would contribute to the development of efficient synthetic methods for biologically active compounds containing a complex structure.
Chapter 1. Total Synthesis of Pachastrissamine (Jaspine B) -- Chapter 2. Total Synthesis of Lysergic Acid, Lysergol, and Isolysergol -- Chapter 3. Conclusions.
Keywords: Bioorganic chemistry; Catalysis; Bioorganic Chemistry; Catalysis